Unraveling Sorghum Canopy Structure’s Genotypic Variability’s Effect on Yield - Matias F. Lucero; Ana J. P. Carcedo; Lucia Marziotte; L. Mayor; Ignacio Antonio Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2024)
Determination of hybrids that are outstanding in performance requires the study of the morphological and phenological characteristics that contribute to crop yield and agronomics. This study explores the performance of 20 sorghum hybrids during the 2022 and 2023 growing seasons in Wamego, Kansas, United States (U.S.), focusing on yield dynamics, crop phenology traits, and canopy structures. Hybrid HYB7 consistently demonstrated superior yields, reaching 157 and 147 bu/a in 2022 and 2023, respectively. Conversely, hybrids ‘HYB4’ to ‘HYB2’ exhibited lower productivity. Principal component analysis highlighted key variables influencing grain yield, revealing positive correlations within grain yield, grain filling duration, leaf length, and leaf width at maturity. Clustering identified three distinct hybrid groups, with Cluster 2 standing out for higher yields. These results provide valuable breeding insights and foundational knowledge for future research evaluating sorghum canopy structure under different climatic conditions.
Keywords: Sorghum bicolor L. Moench; hybrids; canopy architecture; phenology